Política de ações afirmativas de ingresso nos cursos stricto sensu do Centro de Humanidades da Universidade Federal do Ceará: uma avaliação em profundidade - Feitosa, Francisco Renê Fernandes (2024)
Public policies that aim to democratize Higher Education in Brazil, under the premise of comprehensive student training, encouraged the creation of affirmative actions aimed at the entry of postgraduate students into their public universities. In this sense, the research aims to carry out an evaluation of the trajectory of affirmative admission actions implemented in the Postgraduate Programs of the Humanities Center of the Federal University of Ceará, in the city of Fortaleza, between the years 2021 and 2023. Continue in the research uses a qualitative approach, with occasional quantitative input, based on the In-Depth Assessment paradigm defended by Rodrigues (2008), aiming to use structured interviews and content analysis to capture the meanings and paths of the policy in focus, including the analysis of official documents that regulate the policy. Furthermore, the examination of analytical categories relevant to the researched topic is developed, such as structural racism, poverty, people with disabilities, indigenous peoples, ethnic-racial debate, among others. It is concluded that the quota policy within the researched university center, despite advances, needs better development, especially so that it can be strengthened and can promote the retention of benefiting students. In this context, greater attention is needed regarding fraud in vacancies for quota holders, training for hetero-identification boards and protection of the well-being of quota holders in the researched institution.